TensorFlow 2.0 quick start guide : get up to speed with the newly introduced features of TensorFlow 2.0 - Holdroyd, Tony (Packt Publishing, 2019)
TensorFlow is one of the most popular machine learning frameworks in Python. With this book, you will improve your knowledge of some of the latest TensorFlow features and will be able to perform supervised and unsupervised machine learning and also train neural networks.